Partisipasi Perempuan dalam Politik: Antara Representasi dan Kebijakan di Kota Ambon - Tasane, Rican; Manuputty, Feky (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
Women’s participation in politics is a critical issue in democratic discourse, particularly in the context of representation and policy. This article aims to analyze the feminization process occurring in ten political parties in Ambon City during Indonesia’s reform era. Using a qualitative approach, this study collects data from interviews, party statutes and bylaws (AD/ART), as well as documents from the Special Committee on the 2017 Election Bill (RUU Pemilu). The findings indicate that the feminization of political parties in Indonesia can be categorized into two forms: responsive and co-optive feminization. The level of feminization within political parties is influenced by three key factors: the number of women in party structures, the implementation of gender quota regulations, and the party’s response to pro-women policies. This study finds that feminization within political parties in Ambon City remains limited, with a strong tendency towards representation but a negative response in terms of policy. Consequently, the feminization that occurs is more symbolic than a substantive transformation in policy-making. These findings contribute to the study of political feminization by highlighting local dynamics within the Indonesian political context, particularly in archipelagic regions. This research recommends the need for more progressive internal party policy reforms to ensure that women’s increased involvement extends beyond structural representation to meaningful participation in political decision-making with broader impacts.